Introduction to astronomical spectroscopy - Appenzeller, Immo (Cambridge observing handbooks for research astronomers, 2013)
"The book introduces graduate students and young researchers of astronomy and physics to the techniques and methods of astronomical spectroscopy. It covers spectroscopic methods in all branches of astronomy, including optical astronomy, radio astronomy, and astronomy at X-ray and gamma-ray wavelengths. The book will also be of interest for engineers and technicians who are designing or operating optical and space instrumentation"--
Includes bibliographical references and index
Keywords: Spektroskopie; Astronomie